Kreativitas Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa Pada Masa Pandemi COVID-19 Di SMPN 14 Banjarbaru - Saifuddin, Saifuddin (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
This study discusses the creativity of Islamic Religious Education teachers in increasing student learning motivation during the COVID-19 pandemic at SMPN 14 Banjarbaru. The purpose of this study was to determine the creativity of Islamic religious education teachers in increasing student learning motivation during the COVID-19 pandemic at SMPN 14 Banjarbaru and what factors influenced it. The subjects in this study were two teachers of Islamic religious education at SMPN 14 Banjarbaru. While the object in this study is the creativity of Islamic religious education teachers in increasing student learning motivation during the COVID-19 pandemic at SMPN 14 Banjarbaru and the factors that influence it. The author uses the technique of observation, interviews and documentation in data collection. While the data processing technique is done by data classification, editing, and data interpretation. Furthermore, it was analyzed by qualitative descriptive analysis and concluded inductively.Based on the results of the study, it is known that the creativity of Islamic religious education teachers in increasing students' learning motivation during the COVID-19 pandemic at SMPN 14 Banjarbaru has been very good. It can be seen from the teacher being able to create new ideas, being different, flexible, easy to get along with, fun, happy to do experiments and agile in online learning. The factors that influence the creativity of Islamic religious education teachers in increasing student learning motivation during the COVID-19 pandemic at SMPN 14 Banjarbaru include teacher background, teacher teaching experience, teacher personality, teacher welfare and facilities and infrastructure.